Jeevanrekha- Haryana Model for Treatment and Eliminating Hepatitis C - Malhotra, Parveen; Gupta, Usha; Kamboj, Suraj Bhan; Malhotra, Vani; Sanwariya, Yogesh; Chugh, Ajay (Journal of Hematology Research, 2019)
Introduction: The prevalence of chronic hepatitis C virus (HCV) infection has been estimated at between 1.2% and 1.7% in the adult global population whereas estimated figure in India is around 1% but there are no discrete studies for the same. The high cost and long waitlist in developed countries causes unnecessary delay but situation is totally reverse in Haryana, India where with efforts of government, treatment is free of cost to every resident and that too without any waiting period. Review of Literature: HCV, a single stranded RNA can go into chronic phase in 85% of patients and rest can clear this virus on its own. The patients who develop Chronic hepatitis C, after a prolonged period of ten to twenty years can develop cirrhosis in 5-20 % of patients. Few years back, the treatment was given with simple Interferon, followed by Pegylated Interferon & Ribavarin for 24 -48 weeks but after availability of Directly acting antiviral agents (DAA'S), interferon free era of treatment has started since December, 2015 in India. Summary and Conclusions: The main hindrance in treatment of chronic hepatitis C in developed countries is long waiting list and cost of therapy whereas in India, Haryana with help of Jeevan rekha Model, acts of commission has been removed and purchasing is done through open transparent tenders, thus free treatment to every resident has been made available to needy patients for controlling hepatitis C.